Optimalisasi Pengenalan Aplikasi MDIN sebagai Layanan Perbankan Syariah pada Masabah Bank Muamalat Parepare - Mardatillah Mardatillah; Muh Hendra Dwi Saputra; Amin Syam; Hikmadilla Hikmadilla; Nirina Putri Sella; Kasma Kasma; Yasri Tarawiru (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This research aims to optimize the introduction of the MDIN application as one of the sharia banking services offered by Bank Muamalat Indonesia to its customers in Parepare. The MDIN application is designed to provide convenience in digital banking transactions while maintaining sharia principles. The service methods used include outreach, training and assistance to customers. The results of the service show that the introduction of this application increases customers' understanding of digital sharia banking features and increases their interest in using the MDIN application in daily transactions.